(untitled) (Comprehensive Journal of Science, 2026)
This study aimed to identify the impact of e-management, with its dimensions (computers, networks, software, and human resources), on employee performance at the National Commercial Bank, Al-Aziziyah branch. The study employed a descriptive-analytical approach and used a questionnaire as the data collection tool. Due to the limited population, a comprehensive survey was conducted, distributing 31 questionnaires. The study data was analyzed and its hypotheses tested using the SPSS statistical software. The study yielded several results, the most significant being a statistically significant effect (72.9%) of the e-management dimensions (computers, equipment, networks, software, and knowledge creators) on job performance at the National Commercial Bank, Al-Aziziyah branch. This confirmed the study’s main hypothesis. Furthermore, the results showed that the majority of the study sample confirmed a high level of job performance at the National Commercial Bank, Al-Aziziyah branch.